Fullerene-impregnated IRMOFs for balanced gravimetric and volumetric H2 densities: A combined DFT and GCMC simulations study. (18th November 2021) - Yu, Suye; Jing, Guoliang; Zhou, Xuehua; Li, Zhifang; Zhang, Wenqian; Ju, Xin
Abstract: This paper aimed to study the effects of fullerene (C60 ) impregnation on the isoreticular metal-organic framework (IRMOF) materials MOF-650 (ZnO4 nodes were connected to azulenedicarboxylate linkers), MOF-5(ZnO4 nodes were connected to benzenedicarboxylate linkers), and IRMOF-10 (ZnO4 nodes were connected to biphenyldicarboxylate linkers) for H2 storage, these IRMOFs had similar structures but different pore volumes and organic linkers. Density functional theory (DFT) and grand canonical monte Carlo (GCMC) calculations indicated that C60 plays an important role in balancing the gravimetric and volumetric H2 densities of the IRMOFs. The C60 @IRMOFs revealed improved volumetric density when H2 was undersaturated but reduced gravimetric density under H2 saturation. The saturated gravimetric H2 density of the IRMOFs was decided by the free volume. At 77 K, C60 @MOF-650 had a gravimetric H2 density of 5.3 wt% and volumetric H2 density of 42 g/L under 10 bar, and C60 @IRMOF-10 had a gravimetric H2 density of 7.4 wt% and volumetric H2 density of 43 g/L under 18 bar. These values nearly meet the United States Department of Energy (DOE) gravimetric and volumetric H2 density ultimate targets (gravimetric H2 density, 6.5 wt%; volumetric H2 density, 50  g/L) under ambient pressures. Among the studied IRMOFs, C60 @MOF-650 and C60 @IRMOF-10 demonstrated the best H2 storage properties at 233 and 298 K. Highlights: C60 -impregnated IRMOFs demonstrated reduction in saturated gravimetric H2 density. The C60 @IRMOFs revealed improved volumetric density when H2 was undersaturated. C60 @MOF-650 and C60 @IRMOF-10 nearly meet the DOE H2 storage targets.